Analisis Kebutuhan Siswa Terhadap Penggunaan LKPD Interaktif Berbasis Gamifikasi dalam Pembelajaran Matematika SMP SATAP 3 Ponre : Perspektif Psikologi Pendidikan - Mila Karmila; Farida Febrianti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze students' needs for interactive gamification-based worksheets (LKPD) in mathematics at SMP SATAP 3 Ponre. Based on an educational psychology perspective, the study used a qualitative descriptive approach with a case study method through clinical observations over two meetings. The focus of the observations included the subject teacher's activities, student responses, and interactions in the learning environment. The observations indicated that the teacher implemented the learning process quite well through a structured opening, conveying learning objectives, providing stimuli, and using simple media. Students demonstrated quite good engagement, characterized by enthusiasm, participation in answering questions, and the ability to follow each instruction. The learning environment was also quite conducive and supportive of the learning process. However, the educational psychology analysis indicates that learning still has the potential to be optimized through more interactive media to increase intrinsic motivation, active engagement, and a more meaningful learning experience. Therefore, interactive gamification-based LKPD is recommended as an educational technology innovation that meets student needs.